Police Ethics in Rural Contexts: A Left Realist Consequentialist View - Nolan, James J.; DeKeseredy, Walter S.; Brownstein, Henry H. (International Journal of Rural Criminology, 2022)
This article presents crime survey data from the state of West Virginia in the United States showing that, controlling for structural conditions, community atmosphere is significantly related to crime, violence and many other social problems in rural places. These results help identify measurable and achievable progressive desired ends in rural policing, replacing law enforcement outputs (for example, arrests, gun and drug seizures) with safe, strong community outcomes as the summum bonum (i.e, ultimate outcome) of policing. Findings show that interdependent communities where police are partners with residents are the safest, while conflict communities where the police are viewed as adversaries are least safe. These results suggest a left realist consequentialist approach to police ethics to dismantle the hegemony of draconian policies and practices.